Synthesis of Nanocomposites from Pd0 and a Hyper‐Cross‐Linked Functional Resin Obtained from a Conventional Gel‐Type Precursor. Issue 28 (31st May 2013) - Jeřábek, Karel; Zecca, Marco; Centomo, Paolo; Marchionda, Federico; Peruzzo, Luca; Canton, Patrizia; Negro, Enrico; Di Noto, Vito; Corain, Benedetto
Abstract: Hyper‐cross‐linked resins stemming from a gel‐type poly‐chloromethylated poly(styrene‐ co ‐divinylbenzene) resin (GT) have been investigated by a multi‐methodological approach based on elemental analysis, scanning electron microscopy, X‐ray microanalysis, and solvent absorption. The hyper‐cross‐linking of the parent resin was accomplished by Friedel–Crafts alkylation of the phenyl rings of the resins with the chloromethyl groups. This produced a permanent pore system comprising both micropores (<2.0 nm in diameter) and mesopores (2.2 nm). The chloromethyl groups that did not react in the hyper‐cross‐linking step were transformed into methylmercaptan groups and the latter were then converted into sulfonic groups by oxidation with hydrogen peroxide. By this procedure the extensive permanent porosity of the parent unsulfonated hyper‐cross‐linked polymer (HGT) was retained by the sulfonated polymer (HGTS). The final exchange capacity of HGTS was determined to be 0.36 mmol g −1 . HGTS was easily metalated with Pd II and the subsequent reduction of the metal centers with either aqueous sodium borohydride, formaldehyde, or dihydrogen produced three Pd 0 /HGTS nanocomposites. The metal nanoparticles had diameters in the 1–6 nm range for all the nanocomposites, as determined by TEM, but with somewhat different distributions. When formaldehyde was used, more than 90 % of the nanoparticles were less than 3 nm and their radial distribution throughout the polymer beads was quite homogeneous. These findings show that with this reducing agent the metal nanoparticles are generated within the pore system of the polymer matrix, hence their size is controlled by the dimensions of the pores of the polymeric support. Abstract : Templating palladium with a permanently microporous resin : A sulfonated hyper‐cross‐linked resin has been used for the first time as the support for nanostructured palladium. TEM analysis (see figure) showed that the resin effectively acts as an exo‐template that controls the size of the metal nanoparticles generated within its permanent pore system.